The Role of Women Toward the Environment in Ainbo Movie : An Analysis of Ecofeminism - Suci Arwiangsa; Muarifuddin Muarifuddin; Rahmawati Azi (English Literature Study Program, Faculty of Humanities, Universitas Halu Oleo, 2024)
This research aims to explore the role of women in the environment from the perspective of ecofeminism. The researcher uses Karen J. Warren's theory of ecofeminism to determine the level of concern and the role of women in environmental issues. This research employs qualitative methods. The data source for this research is the Ainbo movie. The results show that elements of capitalism, which pursue profit through the relentless exploitation of natural resources and labor, are visible in the practice of illegal gold mining in the Amazon. These activities cause significant environmental damage, and women are often the chief victims of their negative effects. This capitalist system has received strong criticism from the women's movement because, besides promoting environmental degradation, it also exacerbates the oppression of women in the Amazon forest area. The researcher concludes that nature and women have a close relationship, with both often experiencing exploitation. Male characters are depicted as representatives of capitalism who exploit natural resources for personal gain. In contrast, women are depicted as having a deep closeness to nature, reflecting their feminine principles, which emphasize protecting and saving the environment. The role of women as saviors of the environment stands out in contrast to the destructive actions carried out by male capitalists.